2014
DOI: 10.2310/7750.2013.13049
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Dermoscopic Patterns in Lichen Planus: A Case Series from China

Abstract: Background: Dermoscopy has been shown to be a promising method to faciiitate the diagnosis of lichen pianus (LP| outside of China.Objective: To investigate the spectrum of dermoscopic patterns in Chinese LP patients. Methods:The clinical data and dermoscopic patterns of nine LP cases with a total of 43 lesions were evaluated. Results: To the naked eye, 20.97% of the lesions exhibited graying Wickham striae (WS); however, 37.5% presented with white streaks of annular, reticular, or leaf venation patterns under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 7 publications
2
18
0
Order By: Relevance
“…In a study by Zaballos et al , white streaks have been determined in 70% of 10 pilomatrixoma cases [ 10 ]. Similar structures have been observed in juvenile xanthogranuloma and lichen planus [ 11 , 12 ]. White streaks structures have been encountered in pictures of a study about Merkel cell carcinoma although it has not been indicated [ 13 ].…”
Section: Discussionsupporting
confidence: 79%
“…In a study by Zaballos et al , white streaks have been determined in 70% of 10 pilomatrixoma cases [ 10 ]. Similar structures have been observed in juvenile xanthogranuloma and lichen planus [ 11 , 12 ]. White streaks structures have been encountered in pictures of a study about Merkel cell carcinoma although it has not been indicated [ 13 ].…”
Section: Discussionsupporting
confidence: 79%
“…In our study, we detected nine additional WS patterns beyond the “classical reticular” pattern. Leaf venation, circular, and radial streaming patterns were previously defined by Tan et al [ 7 ]. In the current study, leaf venation WS pattern was not detected, but circular and radial streaming WS patterns were detected similar to the Tan et al study.…”
Section: Discussionmentioning
confidence: 99%
“…Dermoscopy findings consist of polymorphic pearly whitish structures that correspond to WS with arboriform “fern leaf” projections. At the borders linear vessels (radial capillaries) and erythematous globules may be observed ( Figure 1 ), WS dermoscopic patterns [ 2 ] ( Table I ): Reticular (the most common) Circular Radial streaming Leaf venation: characterized by delicate secondary striae branching from the centered WS venation, linked together at either end, mimicking the crystal structure of snow Starry sky/white dots: clustered, follicular white dots …”
Section: Discussionmentioning
confidence: 99%